2021
DOI: 10.1210/clinem/dgab046
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Improves Adipose Tissue Insulin Sensitivity in Insulin Resistant Individuals

Abstract: Background Increased tissue cortisol availability has been implicated in abnormal glucose and fat metabolism in patients with obesity, metabolic syndrome, and type 2 diabetes (T2DM). Our objective was to evaluate whether blockade of glucocorticoid receptor (GR) with mifepristone ameliorates insulin resistance (IR) in overweight/obese subjects with glucose intolerance. Methods We conducted a randomized, double-blinded, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The ability of mifepristone to increase life span of virgin females on HFD reported here further extends the similarities between mifepristone effects in flies and mammals. Mifepristone improved insulin sensitivity and adiponectin levels in mice fed a HFD ( Hashimoto et al, 2013 ), and mifepristone is reported to have anti-diabetes and anti-obesity effects in humans and mice ( Gross et al, 2010 ; Bernal-Sore et al, 2018 ; Diaz-Castro et al, 2020 ; Gubbi et al, 2021 ). The female sex-specificity of mifepristone life span effects in Drosophila , and the implication of midgut as a relevant target, also suggests some similarities to human health.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of mifepristone to increase life span of virgin females on HFD reported here further extends the similarities between mifepristone effects in flies and mammals. Mifepristone improved insulin sensitivity and adiponectin levels in mice fed a HFD ( Hashimoto et al, 2013 ), and mifepristone is reported to have anti-diabetes and anti-obesity effects in humans and mice ( Gross et al, 2010 ; Bernal-Sore et al, 2018 ; Diaz-Castro et al, 2020 ; Gubbi et al, 2021 ). The female sex-specificity of mifepristone life span effects in Drosophila , and the implication of midgut as a relevant target, also suggests some similarities to human health.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mifepristone has become of additional interest due to its anti-cancer, anti-obesity, and anti-diabetes effects in human and rodent models [ 3–5 ]. For example, short-term inhibition of the GR with mifepristone was reported to improve insulin sensitivity in overweight and pre-diabetic subjects [ 5 ]. Mifepristone is also a mammalian PPARγ agonist that activates expression of PPARγ target genes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mifepristone is a drug with a long record of safe use in humans for birth control and for the treatment of Cushing's disease, and it has recently become of additional interest because of its anticancer, antiobesity, and antidiabetic effects (Gubbi et al, 2021;Llaguno-Munive et al, 2021). Mifepristone also shows beneficial metabolic effects in female Drosophila, including decreased lipid levels and increased life span on normal and high-fat diets (Landis et al, 2021a;Landis et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone also shows promising results in the treatment of depression (Block et al, 2018). Several studies report antiobesity and antidiabetic effects of mifepristone in humans and mice (Gross et al, 2010;Bernal-Sore et al, 2018;Gubbi et al, 2021). For example, mifepristone improved insulin sensitivity and adiponectin levels in mice fed with a high-fat diet and caused adiponectin release from cultured adipocytes that was dependent upon PPARγ (Hashimoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%